Immersive virtual reality in orthopedic surgery as elective subject for medical students: First experiences in curricular teaching - Schöbel, Tobias; Schuschke, Leonard; Youssef, Yasmin; Rotzoll, Daisy; Theopold, Jan; Osterhoff, Georg (Orthopädie (Heidelberg, Germany), 2024)
Background Virtual reality (VR) simulators have been introduced for skills training in various medical disciplines to create an approximately realistic environment without the risk of patient harm and have improved to more immersive VR (iVR) simulators at affordable costs. There is evidence that training on VR simulators improves technical skills but its use in orthopedic training programs and especially in curricular teaching sessions for medical students are currently not well established. The aim of this study was to describe the implementation of a VR operating theater as an elective course for undergraduate medical students and to evaluate its effect on student learning. Methods An elective course for 12 students was implemented during the summer semester of 2023. Using Oculus Quest 2 headsets (Reality Labs, Meta Platforms, USA) and controllers and the PrecisionOS platform, they were able to train five different surgical procedures. The courses were accompanied by weekly topic discussions and instructional videos. Students were assigned to two groups: group VR vs. group non-VR. The groups were switched after 5 weeks. User feedback and performance development (theoretical and procedural surgical knowledge) after VR training were assessed using three questionnaires. Results The students highly appreciated the implementation of VR training into their curriculum and 91% stated that they would opt for further VR training. All students stated that VR training improved their understanding of surgical procedures and that it should be obligatory in surgical training for undergraduate medical students. After 5 weeks of training, students in the VR group achieved significantly better results (100 out of maximum 180 points) than the non-VR group (70 points, p = 0.0495) in procedural surgical knowledge. After completion of the VR training the VR group achieved 106 points and the non-VR group 104 points ( p = 0.8564). The procedural knowledge for non-VR group after 5 weeks significantly improved after VR training from 70 to 106 points ( p = 0.0087). Conclusion The iVR can be easily integrated into the curriculum of medical students and is highly appreciated by the participants. The iVR statistically improves the procedural knowledge of surgical steps compared to conventional teaching methods. Further implementation of iVR training in curricular teaching of medical students should be considered. Graphic abstract